Synthesis of 3-Aroyl-4-heteroarylpyrrole Derivatives by the Van Leusen Method (2022)
The synthesis and structural diversification of N-heterocycles systems have attracted much attention because of their potential applications. Three 6-aryl-3-methyl-1-phenyl-1H-pyrazolo[3,4- b]pyridine-5-carbaldehyde 4 derivatives, in reaction with acetophenones 5, via conventional Claisen– Schmidt condensation reactions, generated the respective enones. The enones were used as electrondeficient olefins in a “formal” [2+3] cycloaddition reaction using p-tosylmethyl isocyanide—TosMIC 7. This protocol allows access to 3-(substituted aroyl)-4-heteroaryl pyrrole derivatives by the Van Leusen method.